Political economy of the energy-groundwater nexus in India: exploring issues and assessing policy options - Shah, Tushaar; Giordano, Mark; Mukherji, Aditi (Springer, 2012)
Indian agriculture is trapped in a complex nexus of groundwater depletion and energy subsidies. This nexus is the product of past public policy choices that initially offered opportunities to India’s small-holder-based irrigation economy but has now generated in its wake myriad economic, social, and environmental distortions. Conventional ‘getting-the-price-right’ solutions to reduce these distortions have consistently been undermined by the invidious political economy that the nexus has created. The historical evolution of the nexus is outlined, the nature and scale of the distortions it has created are explored, and alternative approaches which Indian policy makers can use to limit, if not eliminate, the damaging impacts of the distortions, are analysed.